Acquiring the Last Plural: Morphophonological Effects on the Comprehension of /-əz. Issue 2 (2nd April 2020) - Davies, Benjamin; Xu Rattanasone, Nan; Demuth, Katherine
ABSTRACT: English-speaking children use plural morphology from around the age of 2, yet often omit the syllabic plural allomorph /-əz/ until age 5 (e.g., bus(es) ). It is not clear if this protracted acquisition is due to articulatory difficulties, low input frequency, or fricative-final words (e.g., bus, nose) being treated as already plural, raising questions about when and how the representation of the syllabic plural develops in perception. Novel-word intermodal preferential looking studies have shown productive comprehension of the plural allomorph /-s/ (e.g., cats ) at 24 months. Using the same procedure, this study investigated when toddlers can comprehend the syllabic plural, and treat words ending in /s, z/ as singular (e.g., bus vs. bus+es ). The results show that 30-month-olds (n = 20) could not identify the number condition of either the singular or plural, but 36-month-olds (n = 20) could identify both, showing productive knowledge of the syllabic allomorph and its singular counterpart with novel words. This suggests children's omission of the syllabic plural in production may be due to later acquired mental representations requiring a sophisticated understanding of English morphophonology.